The Use Of Computer-Aided Interactive Multimedia Learning Media To Increase Learning Motivation And Mathematics Problem Solving Ability - Indu, Novika; Djara, Jean Imaniar (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The success of a learning process can be seen from the level of student mastery of the material being taught. One alternative that can be done to improve students' learning motivation and mathematical problem-solving abilities is to use computer-assisted interactive multimedia learning media. This classroom action research was carried out in two cycles, namely cycle I and cycle II. Each cycle has four stages, namely planning, implementation, observation, and reflection of actions. The actions of each cycle are carried out by conveying learning objectives, motivating students, providing information, students interacting with learning using LCD/computer-assisted interactive multimedia learning projectors on comparative material, students working on LKPD and problem-solving questions, and tests are held at the end of each cycle. The conclusions obtained after the research are as follows: (1) The response of students' learning motivation to the use of multimedia is 73.64% with good criteria, (2) Students' mathematical problem-solving abilities are increasing, this can be seen from the average pretest value = 44.81, cycle I test = 55.19, and cycle II test = 64.42, and posttest = 76.92.